Statistical features and grouping of alfalfa mosaic virus particles - CHEN Ji-shuang; FENG Ming-guang (浙江大学学报. 农业与生命科学版)
One hundred and ninety-six particles of the alfalfa mosaic virus (AMV-SY) previously isolated from Trifolium repens L. was measured under electronic microscope and statistically analyzed. Five groups were distinguished based on the particle lengths measured. The particles in Group I were measured as (20.4±2.5) nm× (18.7±2.3) nm in size, Group Ⅱ (28.0±2.4) nm× (18.1±2.1) nm, Group Ⅲ (36.0±2.4) nm x (17.2±2.0) nm, Group Ⅳ (44.8±2.7) nm× (16.9±2.0) nm, and Group V (52.0±3.0) nm × (17.4±1.0) nm, respectively. The grouping corresponded to the AMV particle types of Ta-t, Ta-b, Tb, M and B previously reported based on X-ray diffraction of the crystallized virions. The lengths in different particle groups were significantly different based on the analysis of variance (F=511.83, P<0.01), and the particle length of Group V was shorter than the length of the type B virions previously reported. The widths also differed significantly among the five groups (F=4.37, P<0.01). The particles in Group I, composed of coat protein subunits alone, was clearly broader than those in Groups Ⅲ and Ⅳ. That indicates that the structure of the particles in Group I is looser than those in other groups due to interaction of coat protein subunits with viral RNA.